Hidden Treasures in the Comoros : The Impact of Inter-Island Connectivity Improvement on Agricultural Production - Iimi, Atsushi (World Bank, Washington, DC, 2019)
The paper revisits the traditional transport-agricultural growth nexus. Connectivity is particularly challenging for small island developing states, such as the Comoros, where domestic markets are limited and transport and transaction costs tend to be high. Using household survey data from Comoros, the paper shows that significant untapped economic potential exists in the domestic market. The analysis shows that better transport connectivity increases crop production and market sales. Accessibility to Moroni, the primary market in the country, and inter-island connectivity are of particular importance. Not only transport infrastructure, but also services are important. Access to intermediary services, such as cooperatives and collectors, is also found to have a positive impact on crop production and market sales.